Faktor-Faktor Yang Mempengaruhi Partisipasi Anggota Pada Koperasi Simpan Pinjam Tawekal Kecamatan Rajapolah Kabupaten Tasikmalaya - Ismi Irpianti Pratami; Yoni Hermawan; Astri Srigustini (JOURNAL SAINS STUDENT RESEARCH, 2023)
This study aims to determine the factors that can influence member participation in the Tawekal Savings and Loans Cooperative. The research method used is a survey method with a quantitative approach. The population in this study were all members of the Tawekal Savings and Loans Cooperative, totaling 321 members. The sampling technique used simple random sampling technique so that a sample of 76 people was obtained. Data collection techniques in this study used questionnaires with multiple linear analysis techniques. The results of the study show that there is a positive and significant influence on cooperative education, cooperative services, cooperative motivation, member satisfaction, the level of member trust, and the business environment on the participation of members of the Tawekal Savings and Loans Cooperative, either partially or simultaneously. The coefficient of determination (R^2) of 0.725 means that 72.5% participation of KSP Tawekal members is influenced by cooperative education, cooperative services, cooperative motivation, member satisfaction, member trust levels, and the business environment. The effective contribution of cooperative education variables is 7,3%, cooperative services are 9,7%, cooperative motivation is 29,7%, member satisfaction is 4,7%, member trust level is 12,2%, and business environment is 8,9% on the participation of KSP Tawekal members.